2016
DOI: 10.1124/jpet.116.232025
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Sodium/Glucose Cotransporter (SGLT) 2 inhibitor Canagliflozin with SGLT1 and SGLT2

Abstract: Canagliflozin, a selective sodium/glucose cotransporter (SGLT) 2 inhibitor, suppresses the renal reabsorption of glucose and decreases blood glucose level in patients with type 2 diabetes. A characteristic of canagliflozin is its modest SGLT1 inhibitory action in the intestine at clinical dosage. To reveal its mechanism of action, we investigated the interaction of canagliflozin with SGLT1 and SGLT2. Inhibition kinetics and transporter-mediated uptake were examined in human SGLT1-or SGLT2-expressing cells. Who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…However, one recent meta‐analysis of data from 23 997 individuals with Type 2 diabetes from 38 randomized controlled trials, found that reductions in HbA 1c , fasting plasma glucose (FPG) and systolic blood pressure (SBP) relative to placebo were greater for canagliflozin 300 mg than for empagliflozin or dapagliflozin . This suggests that canagliflozin may be the agent to beat in terms of efficacy, potentially because of its additional SGLT1 inhibitory effect . However, heterogeneous study designs and variable participant characteristics mean that results should be interpreted with caution.…”
Section: Existing Sglt Inhibitors For Diabetes Mellitusmentioning
confidence: 99%
“…However, one recent meta‐analysis of data from 23 997 individuals with Type 2 diabetes from 38 randomized controlled trials, found that reductions in HbA 1c , fasting plasma glucose (FPG) and systolic blood pressure (SBP) relative to placebo were greater for canagliflozin 300 mg than for empagliflozin or dapagliflozin . This suggests that canagliflozin may be the agent to beat in terms of efficacy, potentially because of its additional SGLT1 inhibitory effect . However, heterogeneous study designs and variable participant characteristics mean that results should be interpreted with caution.…”
Section: Existing Sglt Inhibitors For Diabetes Mellitusmentioning
confidence: 99%
“…Thus, they increase urinary glucose excretion and correct hyperglycaemia. Canagliflozin weakly inhibits SGLT1 in addition to its inhibition of SGLT2 . The renal tubule SGLT1 plays a role glucose reabsorption, which is not reabsorbed by SGLT2 under hyperglycaemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…α‐GIs are used for patients with insulin‐independent postprandial hyperglycaemia who do not exhibit very high fasting blood glucose levels . Furthermore, SGLT2 inhibitors that also inhibit SGLT1 have been recently used . Mitiglinide is combined with these drugs in clinical practice because it is unlikely to negate their effects when used in combination …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further reductions in postprandial glucose also occur through a non‐renal mechanism. While data indicate that canagliflozin does not have systemic effects on SGLT1 (eg, in the kidney, heart or skeletal muscle), the 300‐mg dose may provide transient, local inhibition of SGLT1 in the intestine. This intestinal SGLT1 inhibition may slow glucose absorption from the morning meal and delay the appearance of glucose in plasma .…”
Section: Effects Of Canagliflozin Treatment On Cardiovascular Risk Famentioning
confidence: 97%